Radiation effects on unsteady MHD free convection with Hall current near an infinite vertical porous plate - Mohamed A. Seddeek; Emad M. Aboeldahab (International Journal of Mathematics and Mathematical Sciences)
Radiation effect on unsteady free convection flow of an electrically conducting, gray gas near equilibrium in the optically thin limit along an infinite vertical porous plate are investigated in the presence of strong transverse magnetic field imposed perpendicularly to the plate, taking Hall currents into account. A similarly parameter length scale (h), as a function of time and the suction velocity are considered to be inversely proportional to this parameter. Similarity equations are then derived and solved numerically using the shooting method. The numerical values of skin friction and the rate of heat transfer are represented in a table. The effects of radiation parameter, Hall parameter, and magnetic field parameters are discussed and shown graphically.